Middle-aged adults exhibit altered spatial variations in Achilles tendon wave speed - Slane, Laura Chernak (Physiol Meas, 2015)
The purpose of this study was to investigate spatial variations in measured wave speed in the relaxed and stretched Achilles tendons of young and middle-aged adults. Wave speed was measured from the distal Achilles tendon, soleus aponeurosis, medial gastrocnemius aponeurosis and medial gastrocnemius muscle in healthy young (n = 15, aged 25 ± 4 years) and middle-aged (n = 10, aged 49 ± 4 years) adults in resting, dorsiflexed and plantarflexed postures. In both age groups, Achilles tendon wave speed decreased proximally, with the lowest wave speed measured in the gastrocnemius aponeurosis. Measured wave speed increased with passive dorsiflexion, reflecting the strain-stiffening behavior of tendons. There were no significant aging effects on wave speed in the free tendon or soleus aponeurosis. However, a significant, inverse relationship between gastrocnemius aponeurosis wave speed and age was observed in the dorsiflexed posture. We also observed significantly lower wave speeds in the gastrocnemius muscles of middle-aged adults when compared with young adults. These results suggest that Achilles tendon compliance increases in a distal-to-proximal pattern, with middle-aged adults exhibiting greater compliance in the distal gastrocnemius muscle and tendinous structures. An age-related change in the spatial variation in Achilles tendon compliance could affect localised tissue deformation patterns and injury potential within the triceps surae muscle-tendon units.